Benzos (as) needed: research into as-needed and intermittent benzodiazepines for anxiety is required for comprehensive best prescribing practices - Krieger, Arthur (Frontiers in Psychiatry, 2025)
The medical and public health communities are divided around the use of benzodiazepine (“benzo”) pharmacotherapy for anxiety disorders. Recent years have seen increased attention to benzo overprescription and its risks, leading to a pervasive emphasis on deprescribing. Some have resisted this trend, arguing that the balance of evidence supports the safety and efficacy of benzo pharmacotherapy for both short-term and long-term treatment of anxiety disorders. Given that rising rates of anxiety disorders and benzo misuse are both serious public health concerns, there is an urgent need for comprehensive evidence-based best practices for the prescription of benzos for anxiety. At present, however, major scientific gaps make it impossible to formulate such guidance. Most concerning is the lack of research into as-needed and intermittent prescription and use, which are both what benzos are best suited for, and likely, how they are most commonly administered. Further research into the safety and efficacy of both long-term daily and intermittent, as-needed benzo prescription and use are badly needed. But a roundly “anti-benzo” sentiment may be causing problematic underprescription of benzos, particularly when superior alternatives like cognitive-behavioral therapy are not widely available.